Archery in action bow set-up, tuning and shooting - Needham, Simon S.; Cryer, Nigel; Condie, John; Crowood Films ([Engand, U.K.] : Crowood Films, 2007)
This technical film explains a twelve-point process of setting up the bow. Simon puts a bow together, analysing each aspect that can affect the archer's accuracy. He then explains how to tune the bow to achieve the optimum match between the bow, the arrow and the archer, before advising on how to improve your shooting
Performer: Simon S. Needham
DVD format
Keywords: Archery; Bow tuning (Archery)